2018
DOI: 10.1177/0972262918785962
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media Marketing on Brand Experience: A Study of Select Apparel Brands on Facebook

Abstract: Social media (SM) is an important and emerging area of research, which is of interest to marketers and academicians. Researchers have been studying the impact of social media marketing (SMM) on dimensions such as consumer-based brand equity, purchase intentions, attitudes and others. However, there are insignificant number of studies that have investigated the influence of SMM on brand experience. In this study, content sharing and interaction have been identified as two important marketing activities carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 50 publications
2
43
1
3
Order By: Relevance
“…It means that the third hypothesis is rejected because it does not get significant support by the current findings. These findings are contrary to findings of many past studies, for example, Beig and Khan (2018) and Koay et al (2020) who proved the positive mediation of brand experience between SMMAs and BEQ. These findings are also challenging the findings of some other past studies (e.g., Altaf et al, 2017; Brakus et al, 2009; Dwivedi, 2015; Sahin et al, 2011; Xie et al, 2017) however, this contradiction of findings may be due to the different contexts of studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It means that the third hypothesis is rejected because it does not get significant support by the current findings. These findings are contrary to findings of many past studies, for example, Beig and Khan (2018) and Koay et al (2020) who proved the positive mediation of brand experience between SMMAs and BEQ. These findings are also challenging the findings of some other past studies (e.g., Altaf et al, 2017; Brakus et al, 2009; Dwivedi, 2015; Sahin et al, 2011; Xie et al, 2017) however, this contradiction of findings may be due to the different contexts of studies.…”
Section: Discussioncontrasting
confidence: 99%
“…When consumers perceive that SMMAs of the brand are satisfying their concerns and they have positive perceptions of SMMAs, they are likely to have positive feelings about the brand so, their brand experience is favorable affected. Beig and Khan (2018) also suggested that sharing interesting and informative posts by the marketer of a brand on social media brand page and interactions with customers/followers on regular basis enhance the brand experience of followers towards it. Many other past studies also support this argument because they suggest that direct interactions through such SMMAs tend to enhance the consumer experience (e.g., Brakus et al, 2009; Sahin et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, brands’ content sharing and social interactions positively impact consumers’ sensory, affective, behavioural and intellectual experiences (Beig & Khan, 2018): when a brand communicates or makes an effort to respond to its consumers, they, in turn, feel heightened reassurance (Xie et al., 2017). Thus, timely and thorough communication from corporate in the case of a brand scandal may shape consumers’ attitudes towards the scandal.…”
Section: Theoretical Descriptionsmentioning
confidence: 99%
“…Therefore this article is an effort to understand how perceived threat to online reputation can increase stress levels among youth. And, most of the research has been conducted to study the social media from marketing perspective such as its relationship with constructs such as brand equity (Kim & Ko, 2012; Godey et al, 2016), brand experience (Beig & Khan, 2018), brand romance (Beig & Khan, 2019) consumer behaviour (Ioanăs & Stoica, 2014) etc. But, there is an insignificant research conducted by marketing scholars to study the negative side of the social media (Fox & Moreland, 2015).…”
Section: Introductionmentioning
confidence: 99%